Further exploration of the structure-activity relationship of dual soluble epoxide hydrolase/fatty acid amide hydrolase inhibitors. (1st December 2021) - Wilt, Stephanie; Kodani, Sean; Valencia, Leah; Hudson, Paula K.; Sanchez, Stephanie; Quintana, Taylor; Morisseau, Christophe; Hammock, Bruce D.; Kandasamy, Ram; Pecic, Stevan
Graphical abstract: Abstract: Fatty acid amide hydrolase (FAAH) is a membrane protein that hydrolyzes endocannabinoids, and its inhibition produces analgesic and anti-inflammatory effects. The soluble epoxide hydrolase (sEH) hydrolyzes epoxyeicosatrienoic acids (EETs) to dihydroxyeicosatetraenoic acids. EETs have anti-inflammatory and inflammation resolving properties, thus inhibition of sEH consequently reduces inflammation. Concurrent inhibition of both enzymes may represent a novel approach in the treatment of chronic pain. Drugs with multiple targets can provide a superior therapeutic effect and a decrease in side effects compared to ligands with single targets. Previously, microwave-assisted methodologies were employed to synthesize libraries of benzothiazole analogs from which high affinity dual inhibitors (e.g. 3, sEH IC50  = 9.6 nM; FAAH IC50  = 7 nM) were identified. Here, our structure-activity relationship studies revealed that the 4-phenylthiazole moiety is well tolerated by both enzymes, producing excellent inhibition potencies in the low nanomolar range (e.g. 6o, sEH IC50  = 2.5 nM; FAAH IC50  = 9.8 nM). Docking experiments show that the new class of dual inhibitors bind within the catalytic sites of both enzymes. Prediction of several pharmacokinetic/pharmacodynamic properties suggest that these new dual inhibitors are good candidates for further in vivo evaluation. Finally, dual inhibitor 3 was tested in the Formalin Test, a rat model of acute inflammatory pain. The data indicate that 3 produces antinociception against the inflammatory phase of the Formalin Test in vivo and is metabolically stable following intraperitoneal administration in male rats. Further, antinociception produced by 3 is comparable to that of ketoprofen, a traditional nonsteroidal anti-inflammatory drug. The results presented here will help toward the long-term goal of developing novel non-opioid therapeutics for pain management.